2020
DOI: 10.4236/ojneph.2020.101006
|View full text |Cite
|
Sign up to set email alerts
|

Non-Infectious Complications of Peritoneal Dialysis in Senegal

Abstract: Introduction: Senegal has pioneered the implementation of peritoneal dialysis (PD) in West Africa, practicing it since 2004. Non-infectious complications are a significant cause of failure of this technique and the transfer of patients to haemodialysis. The aim of this study was to determine the prevalence and the different types of non-infectious complications in our context. Patients and Methods: This was a 5-year, descriptive, retrospective study of patients on chronic peritoneal dialysis for more than 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Patients on PD must have a toilet in the home for disposing of dialysate and cleanliness requirements generally when applying PD requires clean water [ 52 ]. A study conducted in Senegal which looked at non-infectious complications of PD reported that mechanical complications such as catheter migration and metabolic complications such as hypoalbuminemia could be corrected by having experienced staff members inserting catheters and giving good nutritional advice before serious complications arise [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients on PD must have a toilet in the home for disposing of dialysate and cleanliness requirements generally when applying PD requires clean water [ 52 ]. A study conducted in Senegal which looked at non-infectious complications of PD reported that mechanical complications such as catheter migration and metabolic complications such as hypoalbuminemia could be corrected by having experienced staff members inserting catheters and giving good nutritional advice before serious complications arise [ 53 ].…”
Section: Discussionmentioning
confidence: 99%